Preventing adolescent suicide: A systematic review of the effectiveness and change mechanisms of suicide prevention gatekeeping training programs for teachers and parents. (1st May 2019) - Torok, M.; Calear, A.L.; Smart, A.; Nicolopoulos, A.; Wong, Q.
ABSTRACT: Introduction: Suicide is a leading cause of death in young people, which may in part be because young people are notoriously poor help‐seekers. Improving the identification of at‐risk young people and connecting them to appropriate help is needed to prevent suicide in adolescents. The aim of this study is to examine the effectiveness of suicide prevention gatekeeper programs for parents and teachers, which are designed to improve their ability to recognise and respond to risks so that they may intervene before crisis occurs. Methods: Academic databases and reference lists were searched for gatekeeper training programs involving teachers and parents, and which aimed to prevent youth suicide, between journal inception and May 2018. Information directly reporting on suicide literacy (knowledge, confidence, attitudes) and/or gatekeeper behaviours (identification, referral) was extracted and a qualitative synthesis was conducted. Results: Thirteen studies fulfilled inclusion criteria. Significant moderate‐to‐large intervention effects were reported for suicide literacy outcomes among teachers and parents, with the largest gains among those with lowest baseline scores. No improvements in identification and referral behaviors among gatekeepers were noted. A need to improve evaluation research designs and outcome measurements was evident. Conclusions: While gatekeeper programs lead to increased suicide literacy, there is little evidence for behavioural change. There is need to increase the reach and uptake of gatekeeper training by offering digital versions, which may lead to improved behavioural outcomes, and to employ targeted strategies to engage parents in this training as one of the most trusted sources of support for vulnerable youth.